2020
DOI: 10.1155/2020/1972064
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of Novel Clinical Prognosis Nomograms for Luminal A Breast Cancer Patients with Bone Metastasis

Abstract: Purpose. Overall survival (OS) and cancer-specific survival (CSS) of luminal A breast cancer (BC) patients with bone metastasis remain poor and vary dramatically from person to person. Our goal was to build two universally applicable nomograms to accurately predict OS and CSS for luminal A patients with bone metastasis. Methods. The data were collected from the Surveillance, Epidemiology, and End Results (SEER) database for luminal A BC patients with bone metastasis between 2010 and 2015. Univariate and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A significant difference in survival was not revealed among various races, which was congruent with some previous studies ( 13 , 17 ). However, other studies found race was an independent prognostic factor among BC with bone metastasis ( 15 , 16 ). Tumor grade is usually recognized as an independent risk factor for the prognosis of BC ( 16 , 18 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A significant difference in survival was not revealed among various races, which was congruent with some previous studies ( 13 , 17 ). However, other studies found race was an independent prognostic factor among BC with bone metastasis ( 15 , 16 ). Tumor grade is usually recognized as an independent risk factor for the prognosis of BC ( 16 , 18 ).…”
Section: Discussionmentioning
confidence: 85%
“…On the whole, the prognosis of male BC with bone metastasis (3-year OS and CSS rates: 36.7% and 39.5%) was worse than that of female patients (3-year OS and CSS rates: 51.7% and 53.6%) ( 13 ), suggesting that the prognosis and treatments of such patients need more attention. Previous studies indicated that older BC patients were prone to bone metastasis ( 14 ) and age was an important independent predictor of survival ( 15 , 16 ). Our multivariable results also highlighted this finding in male BC patients with bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is an intuitive graphical prediction model that provides an accurate, personalized prediction of risk for each individual. 16 Although several nomograms have been established for NAFLD, to our knowledge, a nomogram that predicts the 2-year risk of NAFLD in the non-obese population with normal blood lipid levels has not been reported. Therefore, in this study, we developed and validated a nomogram based on independent predictors to better assess the 2-year risk of NAFLD in the non-obese population with normal blood lipid levels.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicopathological data, laboratory tests, and genomic data were confirmed as prognostic predictors for BCBM patients, [8][9][10][11][12][13][14][15][16] and several studies aimed to develop prognostic nomograms for BCBM patients. 6,[16][17][18][19] However, elderly BC patients have their own unique characteristics, which suggested that we need to conduct a specific study for this special population. [20][21][22] In this study, we obtained population-based data of BC patients to investigate the characteristics of elderly BC patients and aimed to establish two novel nomograms to predict the overall survival (OS) and cancer-specific survival (CSS) of elderly BCBM patients.…”
Section: Introductionmentioning
confidence: 99%